(untitled) (Academic Journal of Internal Affairs, 2021)
Lifelong learning is an integral part of the Hungarian education strategy in line with EU guidelines. In line with the maintenance of learning abilities, the school movement culture in the form of everyday physical education has also entered the Hungarian education system. The latter has been proven to have a distinctly beneficial effect on learning processes by a number of researches and studies. Anders Hansen’s book presents and explains the effects of everyday movement on the brain through practical examples. These simple exercises and daily habits can be done at all ages without the need of tools. And their effects are interpreted in plain language by the author, using the latest neuroscientic findings.